The Influence of Product Placement on Brand Awareness of Ellips Hair Vitamin on Indonesia's Next Top Model Youtube Channel - Emilia Emilia (Inovbiz: Jurnal Inovasi Bisnis, 2021)
This research is conducted based on the phenomenon of Indonesia’s Next Top Model (further abbreviated to INTM) on YouTube which appearing the product of Ellips hair vitamin and the appearance is continuously being talked about by viewers on social media. No wonder, it seems to impact the activity of social media of Ellips itself. The research aims at finding out whether product placement influences brand awareness of Ellips hair vitamin or not. The quantitative method in this research is engaged by using a questionnaire instrument spread to the population which is the subscribers of Indonesia's Next Top Model on YouTube. The questionnaires are shared to a hundred samples gained by systematic random sampling technique. A series of tests are also conducted, namely data analysis test by using classic assumption tests, correlation coefficient test, determination coefficient test, simple linear regression test, and hypothetical test. The result shows that the activity of product placement influences positively and significantly on Ellips brand awareness as well as having a strong and direct relationship. The variable of product placement and brand awareness has a good recapitulation value of percentage which is above 80% of the whole dimension from both variables. By keeping on going on remarkable performance on product placement, it will also increase brand awareness of Ellips. To conclude, the next activities on product placement shall choose which media or program that is more attractive or engaging to the viewers accordingly to the target market of Ellips